Brazilian Pseudochironomini (Diptera: Chironomidae) Part 1. New Pseudochironomus Malloch from highlands - Shimabukuro, Erika Mayumi; Pepinelli, Mateus; Trivinho-Strixino, Susana (Zootaxa, 2017)
Four new species of Pseudochironomus Malloch were recorded in Brazilian highlands, three from Atlantic forest and one from Amazon Forest. Adult males and immature stages of Pseudochironomus ruah sp. n., P. jordensis sp. n. and adult males of P. mocidade sp. n., P. surianae sp. n. are described and illustrated. Adult males and females of P. ruah sp. n. were associated using DNA barcodes along with a NJ tree for all Pseudochironomini barcoding sequences publicly available. An emendation to generic diagnoses is provided, once it is the first time that thoracic acrostichals have been described for Pseudochironomus species.